2017
DOI: 10.1159/000485898
|View full text |Cite
|
Sign up to set email alerts
|

Type-Specific Human Papillomavirus Prevalence in Iranian Women with Normal Cervical Cytology: The Impact of Current HPV Vaccines

Abstract: Objective: Human papillomavirus (HPV) vaccination is currently not included in the national vaccination program in Iran. Regional data on the distribution of HPV types in women are important as they can predict the impact of currently available vaccines and help health policy makers to consider all the possibilities with regard to HPV vaccination. Methods: A total of 1,218 Iranian women with normal cervical cytology were included in this study. The presence of the HPV genome was investigated in all specimens b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 27 publications
0
21
0
Order By: Relevance
“…HPV 16 and HPV 18 are the most prevalent HPV genotypes in women with normal Pap smear and cancerous samples [ 20 , 21 ]. Although the burden of HPV 16 and HPV 18 has reduced following vaccination, their potential contribution to cancer progression remains unchanged.…”
Section: Discussionmentioning
confidence: 99%
“…HPV 16 and HPV 18 are the most prevalent HPV genotypes in women with normal Pap smear and cancerous samples [ 20 , 21 ]. Although the burden of HPV 16 and HPV 18 has reduced following vaccination, their potential contribution to cancer progression remains unchanged.…”
Section: Discussionmentioning
confidence: 99%
“…After intravenous anesthesia, the patients in the lithotomy position received local anesthesia in the cervix at four time-points (3,6,9, and 12 hours) with 2% xylocaine without vasoconstrictor using 2 ml per point. Then the LEEP was performed, hemostasis was performed with a roller-ball electrode, the cervix was dilated to Hegar number 8, and DUDA was placed (Figs 1 and 2) on the cervix and secured with four Prolene 2-0 stitches in the DUDA group.…”
Section: Surgical Proceduresmentioning
confidence: 99%
“…In most cases, after 6 to 12 months of infection, the immune system eliminates the virus. If the lesion persists, women may develop cancer precursor lesions in the cervix and, if not treated, cervical cancer [1][2][3][4]. The term used for cervical precursor lesions or high-grade cervical intraepithelial neoplasia (CIN) is used to define lesions previously reported as moderate dysplasia (CIN II) and severe dysplasia/carcinoma in situ (CIN III) [5].…”
Section: Introductionmentioning
confidence: 99%
“…Among high-risk HPV types, HPV 16 and 18 are leading cause and responsible for almost 72% of cervical cancer [7]. Most studies on the prevalence of HPV types has indicated that HPV 16 and 18 are the most prevalent types in women with normal cervical cytology and invasive cervical cancer in Iran [8][9][10][11][12][13]. A meta-analysis was revealed that the five most common HPV types are HPV 16,18,31,39, and 45 in Iranian women with cervical cancer [14].…”
Section: Introductionmentioning
confidence: 99%